Technical-Economic Characteristics of Small-Scale Troll Line Fishing in the Small Island Park Conservation Area of Kei Kecil, Southeast Maluku Regency - Picaulima, Simon M; Makailipessy, Marvin M; Thenu, Imanuel M; Ngamel, Anna K (Jurnal Perikanan dan Kelautan, 2025)
The troll line fishery developing in the TPK Kei Kecil conservation area is a small-scale fishery consisting of 2 types, bottom and surface troll line. Both kinds of troll lines have technical differences. These technical differences will impact the type of catch and income of the troll line fishermen. This study examines the technological-economic characteristics of small-scale surface and bottom troll line fisheries in the TPK Kei Kecil conservation area. Primary and secondary data are needed, and the data is collected using a survey method with triangulation techniques. The analysis used is qualitative descriptive analysis for the technological aspect and quantitative analysis for the economic aspect. The analysis results show that the construction of surface and bottom troll line fishing technology has differences in ship construction, fishing gear, fishing methods, and different fishing seasons, as well as impacts on the types of target fish. Economically, bottom troll line fishing using a 15 HP outboard motor propulsion is more economical in the west season, and surface troll line fishing using a 15 HP outboard motor propulsion and 6.5 HP trolling is more economical in the east season; therefore, troll line fishing fisheries management needs to be carried out adaptively